Exiles: A Play in Three Acts - Joyce, James, 1882-1941 (Salt Lake City, UT : Project Gutenberg, 2017)
"Exiles: A Play in Three Acts" by James Joyce is a play written in 1915. Joyce's only extant drama follows writer Richard Rowan and his common-law wife Bertha as they return to Ireland from Rome. There they reunite with old friends Robert Hand and Beatrice Justice, igniting tensions of jealousy and desire. When Robert attempts to seduce Bertha, Richard insists she must choose freely. The play explores questions of human freedom, dignity, and sexual relationships through ambiguous encounters that leave both characters and audience uncertain about what truly transpired. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Exiles_(play)
Release date is 2017-11-12
Produced by Menno de Leeuw
Keywords: Alienation (Social psychology) -- Drama; Domestic drama; Authors -- Drama; Dublin (Ireland) -- Drama